2019
DOI: 10.1371/journal.pone.0216041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton pump inhibitors on mortality of cirrhotic patients with pneumonia

Abstract: Objective Pneumonia is life-threatening in patients with liver cirrhosis. Proton pump inhibitors (PPIs) may increase the risk of these patients developing pneumonia. However, whether PPIs increase mortality in patients with cirrhosis and pneumonia remain unknown. Methods We used the Taiwan National Health Insurance Database to enroll 1,201 cirrhotic patients with pneumonia without active gastrointestinal bleeding who were receiving PPIs and were hospitalized between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The study was not designed explicitly to examine the risk of pneumonia. In a mortality study of cirrhotic patients with pneumonia, but not active gastrointestinal bleeding, PPIs were not associated with 30 day mortality [179]. However, the authors stated that prolonged PPI therapy may be associated with higher mortality.…”
Section: Microbiological Consequences Of Removing Gastric Acidmentioning
confidence: 99%
“…The study was not designed explicitly to examine the risk of pneumonia. In a mortality study of cirrhotic patients with pneumonia, but not active gastrointestinal bleeding, PPIs were not associated with 30 day mortality [179]. However, the authors stated that prolonged PPI therapy may be associated with higher mortality.…”
Section: Microbiological Consequences Of Removing Gastric Acidmentioning
confidence: 99%
“…An early meta-analysis published in 2015 showed that PPI use was not associated with increased mortality in patients with cirrhosis [11]. However, only four cohort studies [14,16,17,19] were included in the present study, and many related cohort studies have been published since the previous meta-analysis [18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In addition, it remains unknown…”
Section: Introductionmentioning
confidence: 89%
“…Overall, 21 cohort studies with 20,899 patients and 7457 death events were included, of which 16 were retrospective cohort studies [16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33], while the other five were prospective cohort [14,15,20,21,34]. As for the ethnicity of the patients, 12 studies included Caucasian patients [15,16,18,[20][21][22]24,28,29,[32][33][34], 7 included Asians [17,19,23,25,26,30,31], and the remaining 2 included patients with mixed ethnicity [14,27]. Most of the studies included patients with hospitalized patients with cirrhosis without serious clinical complications [14][15][16][17][18]…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations